Aspergilloma pada Tuberkulosis Paru: [Aspergilloma in Pulmonary Tuberculosis: A Case Report] - Soedarsono Soedarsono; Elisabeth Tri Wahyuni Widoretno (Faculty of Medicine Universitas Airlangga, 2017)
The incidence of lung aspergillosis increases year to year. Lung aspergilloma is the most recognizable form of aspergillosis. Since 1980, the most common condition for initiating aspergillosis is tuberculosis (TB). Untreated pulmonary TB can cause several complications, such as decreases of pulmonary function, persistent pulmonary symptoms and Chronic Pulmonary Aspergillosis (CPA). More than 90% Aspergillosis is caused by Aspergillus fumigatus, this type is also widely found in people with TB. This type of fungus has a simple biological cycle with high sporulation capacity, which causes the release of conidia into the atmosphere with high concentrations. Humans inhale hundreds of conidia each day. Immuno competent hosts are capable of destroying conidia with the pulmonary immune system. Aspergillus infections cause illness when the host response is too strong or weak to the aspergillus antigen. The CPA morbidity rate is quite large with systemic symptoms and respiratory symptoms due to progressive pulmonary fibrosis and diminished lung function. During treatment, the CPA has a fatality rate of 20-33% in the short term and more than 50% in the span of 5 years. The Research Committee of the British Tuberculosis Association found that patients with post-TB cavity had a high risk of fungal colonization. The cavity formed in pulmonary TB is a suitable place for the development of various organisms including the fungus because it contains enough oxygen and necrotic tissue. The most common form of CPA associated with TB is Aspergilloma. In this review we will focus on aspergilloma, its diagnosis and management.